MATHEMATICAL MODEL OF FILING MEDIUMS AS FUNCTION OF A REFRACTIVITY - Turlybekova, G. K.; Kusainov, S. G. (Recent Contributions to Physics, 2008)
In operation influence of properties of a medium, on such parameter as a refractivity n describing a phase velocity of a wave, and also association - is shown, to inductivity and  - to a magnetic conductivity not only on an absolute value of them, but also on a sign which the refractivity can accept the bound with them the formula n = -  that is his negative value.Operation as is bound with holography optical devices and their solving capacity, examination which authors of operation are engaged. This functional connection is submitted as mathematical model circumscribed by the constitutive equation of electrodynamics and the relevant constitutiveequations which is necessary for taking into account in this case for a solution of a task in view.